The Effectiveness of Ethnoscience Learning: Perception of Science Teacher Candidates - Desi Ratnasari; M. Khairul Wazni; Suhirman Suhirman; M. Yamin; Agus Muliadi (Postgraduate, University of Mataram, 2024)
Study aims to explore the science teacher candidates regarding the effectiveness of ethnoscience learning. This study is an exploratory research conducted at the Mandalika University of Education with research subjects of 28 biology education students. This research uses a research instrument in the form of a closed questionnaire with answers using a Likert scale and has been validated by experts. This research data was analyzed using quantitative descriptive statistics and inferential statistics with independent sample t-test. The study results show that (1) The perception of prospective science teacher students regarding the effectiveness of ethnoscience learning has an average score of 2.98 in the Tall category, while based on gender, the average score for male students is 3.13 with the Tall category and for women it is 2.91 with Tall category; (2) there is no significant difference in the perceptions of male and female students regarding the effectiveness of ethnoscience learning as evidenced by a significance value of 0.116 which is greater than 0.05 (>0.05).